Spin freezing and magnetic inhomogeneities in bilayer manganites. - Coldea, A; Blundell, S; Steer, C; Mitchell, J; Pratt, F (2002)
We have performed a muon spin rotation study on polycrystalline samples of electron-doped layered manganites, La2-2xSr1+2xMn2O7 (0.4< or =x<1), in order to investigate the local magnetic structure and spin dynamics. Our results provide evidence for phase separation into A-type antiferromagnetic and charge-ordered phases for x=0.52 and spin freezing at low temperatures (T<100 K) for 0.52< or =x<0.75. A new phase diagram which includes this spin-freezing region is proposed.